UMPSA signs MoA with Volkswagen Group Malaysia Sdn. Bhd. - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 12 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) signed a memorandum of agreement (MoA) with the world’s leading automotive brand, Volkswagen Group Malaysia (VGM), to establish bilateral strategic collaboration.